Upaya Pemadaman Kebakaran Hutan Dan Lahan Menggunakan Gel Pemadam (Gel Pack Extinguishing Agent) - Bambang Hero Saharjo; Irbah Imtinan (Jurnal Silvikultur Tropika, 2019)
Forest and land fires become serious problems in Indonesia that could not be well managed until today. This is then the reasons why there is so many activties being conducted in order to find the best solution including fire suppression method. Until today the suppresion methods mostly using water rather than other sources, which actually is not so effective and efficient. The research is proposed to make sure that Gel Pack Extinguishing Agent (GPEA) could be used for fire suppression. Three different fuels used were Pinus merkusii, Shorea leprosula, and Dicranopteris linearis at different of 55g, 65g, 75g, dan 85g. The results of research shown that GPEA with 5 small box per litter of water was the best dosage. The fastes suppression time based on the three fuels was Dicranopteris linearis, and the lowest was Pinus merkusii.Keywords: fuels, forest and land fires, Gel, suppresion methode, dosage